Juror Stereotypes and Blame Attribution in Rape Cases Involving Intoxicants: The Findings of a Pilot Study - Finch, Emily (The British journal of criminology, 2005)
Prior to recent legislative changes, sexual offences were contained in a combination of statutory provisions and common law that was criticized as being ill-equipped to tackle the intricacies of modern sexual (mis)behaviour. This pilot study explored the capacity of these provisions to address the complexities of drug-assisted rape using focus groups and a trial simulation to identify factors which influenced jurors in rape trials involving intoxicants. The findings revealed that jurors considered numerous extra-legal factors when reaching a decision: rape myths, misconceptions about the impact of intoxicants and factors such as the motivation of the defendant in administering an intoxicant. This paper draws upon these findings, focusing in particular on the interaction between juror attributions of blame and stereotypical conceptions about intoxication, sexual consent and drug-assisted rape. The findings of this pilot study form the basis for a larger-scale project (ESRC -funded, commenced January 2004) that examines this interaction in the context of new provisions under the Sexual Offences Act 2003